2015
DOI: 10.1515/cpe-2015-0015
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Studies on Controlling Gaseous Fuel Combustion by Managing the Combustion Process of Diesel Pilot Dose in a Dual-Fuel Engine

Abstract: Protection of the environment and counteracting global warming require finding alternative sources of energy. One of the methods of generating energy from environmentally friendly sources is increasing the share of gaseous fuels in the total energy balance. The use of these fuels in compression-ignition (CI) engines is difficult due to their relatively high autoignition temperature. One solution for using these fuels in CI engines is operating in a dualfuel mode, where the air and gas mixture is ignited with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Because of this, the research tilts biogas (BG) compression ignition engines [42]. The pilot dose is diesel fuel (DF) and the main fuel is biogas [42,43]. It was found that the proportion of BG in fuel has a positive effect on the level of harmful gas emissions but slightly lowers the efficiency of the engine at full load [44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this, the research tilts biogas (BG) compression ignition engines [42]. The pilot dose is diesel fuel (DF) and the main fuel is biogas [42,43]. It was found that the proportion of BG in fuel has a positive effect on the level of harmful gas emissions but slightly lowers the efficiency of the engine at full load [44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…Because the biogas obtained in practice is characterized by the variable content of methane, carbon dioxide, and hydrogen sulphide, research is conducted in which the gas composition is simulated in order to discover phenomena and dependences having a significant impact on toxic exhaust components [55][56][57][58]. However, after analyzing the literature [42,43,59,60], one cannot get an unambiguous answer to the question of whether the solution is pro-ecological.…”
Section: Introductionmentioning
confidence: 99%
“…5. Achieved accuracy vs. computation efficiency allow to conclude that the model is capable of supporting major phases of DF combustion engine development, i. e.: concept study support (some trend prediction capabilities using the model had already been shown in [27]), control development (the model can anticipate system reaction on air-path and injection system excitations and therefore support designing control strategies, also transients prediction is possible when combine with a proper air-path model) and model-assisted calibration (the model accuracy allows for pre-determining controller parameters which can serve as basis for experimental fine-tuning calibration). For model based control the model is still to slow for direct implementation.…”
Section: Discussionmentioning
confidence: 89%
“…While injecting the liquid fuel the thermodynamic parameters of the medium are changed. The effect of the mass stream of the fuel injected into the cylinder was modelled with the aid of the Mikulski et al [27] original correlation based on a normal distribution.…”
Section: The 0-dimensional Dual-fuel Engine Modelmentioning
confidence: 99%
See 1 more Smart Citation